Penerapan Strategi Perataan Laba pada Industri Manufaktur: Studi Literatur - Wulandari, Aulia Putri (Universitas Muhammadiyah Gresik, 2025)
This study explores the application of earnings smoothing strategies in the manufacturing industry through a literature review approach. Earnings smoothing is commonly used by management to reduce profit volatility and present more stable financial reports to external stakeholders. The manufacturing sector is particularly prone to income fluctuations due to complex operations and high production costs, making it a frequent context for such practices. The study finds that motivations for earnings smoothing include meeting investor expectations, reducing regulatory scrutiny, and maintaining stock price stability. Common methods involve accrual-based adjustments and real transaction timing. Factors such as firm size, profitability, audit quality, and governance structure influence the likelihood of earnings smoothing. While it can enhance financial predictability in the short term, excessive use may mislead users and harm transparency. This review highlights the importance of oversight to ensure the credibility of financial reporting.